Spinal muscular atrophy caused by a novel Alu‐mediated deletion of exons 2a‐5 in SMN1 undetectable with routine genetic testing. Issue 7 (26th April 2020) - Jedličková, Ivana; Přistoupilová, Anna; Nosková, Lenka; Majer, Filip; Stránecký, Viktor; Hartmannová, Hana; Hodaňová, Kateřina; Trešlová, Helena; Hýblová, Michaela; Solár, Peter; Minárik, Gabriel; Giertlová, Mária; et al.
Abstract: Background: Spinal muscular atrophy (SMA) is an inherited neuromuscular disease affecting 1 in 8, 000 newborns. The majority of patients carry bi‐allelic variants in the survival of motor neuron 1 gene ( SMN1 ). SMN1 is located in a duplicated region on chromosome 5q13 that contains Alu elements and is predisposed to genomic rearrangements. Due to the genomic complexity of the SMN region and genetic heterogeneity, approximately 50% of SMA patients remain without genetic diagnosis that is a prerequisite for genetic treatments. In this work we describe the diagnostic odyssey of one SMA patient in whom routine diagnostics identified only a maternal heterozygous SMN1Δ(7–8) deletion. Methods: We characterized SMN transcripts, assessed SMN protein content in peripheral blood mononuclear cells (PBMC), estimated SMN genes dosage, and mapped genomic rearrangement in the SMN region. Results: We identified an Alu ‐mediated deletion encompassing exons 2a‐5 of SMN1 on the paternal allele and a complete deletion of SMN1 on the maternal allele as the cause of SMA in this patient. Conclusion: Alu ‐mediated rearrangements in SMN1 can escape routine diagnostic testing. Parallel analysis of SMN gene dosage, SMN transcripts, and total SMN protein levels in PBMC can identify genomic rearrangements and should be considered in genetically undefined SMA cases. Abstract : Spinal muscular atrophy (SMA) is devastating inherited neuromuscular disease resulting from variants of SMN1 and deficiency of the survival motor neuron protein (SMN). In this work, we describe the diagnostic odyssey for one SMA patient in whom routine diagnostic procedures identified only a heterozygous, maternally inherited deletion of exons 7 and 8 in SMN1. Using an individual approach we found in this case that SMA was caused by a novel Alu‐mediated deletion.